2023
DOI: 10.1111/jvim.16747
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet composition on glandular gastric disease in horses

Abstract: Background Nutritional factors are suggested to influence the incidence and severity of glandular gastric disease (GGD) in horses. Objectives To retrospectively assess whether dietary fermentable carbohydrates increase the severity of GGD and to prospectively evaluate whether the partial substitution of concentrates by dehydrated alfalfa would decrease GGD severity scores. Animals In total, 82 trotters from 4 training centers exercised ≥5 days/week. Methods Multicenter retrospective observational study, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
0
0
1
Order By: Relevance
“…In the present study, in horses with lesions of the glandular mucosa, feeding alfalfa was associated with an increased risk of disease. This is contrary to a recent study, where pelleted alfalfa was found to be protective for EGGD [ 35 ]. Another study, though, found that feeding alfalfa as chaff in weanlings increased the number of lesions in the pylorus area compared to feeding pellets; both formulations did not improve the score of the gastric lesions [ 36 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, in horses with lesions of the glandular mucosa, feeding alfalfa was associated with an increased risk of disease. This is contrary to a recent study, where pelleted alfalfa was found to be protective for EGGD [ 35 ]. Another study, though, found that feeding alfalfa as chaff in weanlings increased the number of lesions in the pylorus area compared to feeding pellets; both formulations did not improve the score of the gastric lesions [ 36 ].…”
Section: Discussioncontrasting
confidence: 99%